1993
DOI: 10.1128/jb.175.18.5899-5906.1993
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolar mutagenesis of the ipa genes defines IpaB, IpaC, and IpaD as effectors of Shigella flexneri entry into epithelial cells

Abstract: A 31-kb fragment of the large virulence plasmid of Shigella flexneri is necessary for bacterial entry into epithelial cells in vitro. One locus of this fragment encodes the IpaA, -B, -C, and -D proteins, which are the dominant antigens of the humoral immune response during shigellosis. To address the role of the ipa genes, which are clustered in an operon, we constructed a selectable cassette that does not affect transcription of downstream genes and used this cassette to inactivate the ipaB, ipaC, and ipaD ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
594
0
7

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 687 publications
(611 citation statements)
references
References 39 publications
(31 reference statements)
10
594
0
7
Order By: Relevance
“…Accordingly, the efficiency of ruffle formation, i.e., the percentage of ruffles induced upon bacterial contact, was similar in cells treated with stressors and control cells (Appendix Fig S1G). To uncouple Shigella binding to host cells from subsequent steps of invasion, we performed parallel experiments with the Shigella Δ ipaB mutant strain, which binds efficiently to host cells but is unable to invade (Menard et al , 1993). Treatment of cells with arsenite or anisomycin inhibited binding of Shigella Δ ipaB , similar to the WT bacteria (Fig 2A–E, and Appendix Fig S1B, C, E and F).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the efficiency of ruffle formation, i.e., the percentage of ruffles induced upon bacterial contact, was similar in cells treated with stressors and control cells (Appendix Fig S1G). To uncouple Shigella binding to host cells from subsequent steps of invasion, we performed parallel experiments with the Shigella Δ ipaB mutant strain, which binds efficiently to host cells but is unable to invade (Menard et al , 1993). Treatment of cells with arsenite or anisomycin inhibited binding of Shigella Δ ipaB , similar to the WT bacteria (Fig 2A–E, and Appendix Fig S1B, C, E and F).…”
Section: Resultsmentioning
confidence: 99%
“…For construction of a nonpolar spa32 mutant, the aphA-3 (kanamycin resistance gene) cassette specifically designed for the construction of a nonpolar mutant was used (31). The aphA-3 cassette carried by plasmid pUC18K2 was obtained from Philippe J. Sansonetti (Institut Pasteur, Paris, France).…”
Section: Methodsmentioning
confidence: 99%
“…Construction of kanamycin (aphA-3) cassette insertions Each ORF was disrupted by inserting the non-polar aphA-3 cassette, which confers kanamycin resistance (Menard et al, 1993), into a restriction enzyme site within the coding sequence as shown in Fig. 1.…”
Section: Dna Sequencing and Analysismentioning
confidence: 99%